Pengaruh Inovasi Produk dan Keunggulan Bersaing terhadap Keberhasilan Usaha pada UMKM Industri Makanan dan Minuman di Kota Medan - Fajar Mulia; Warsani Purnama Sari; Alfriado Leonard Noprian Dolok Saribu; Wardhani Indah Sari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to determine the influence of product innovation and competitive advantage on business success in Food Industry MSMEs in Medan City. The MSME Food and Beverage Industry is one of the businesses most in demand by young entrepreneurs. However, there are also risks in running this business due to extensive competition in the Food and Beverage Industry, where many MSMEs in the Food and Beverage Industry experience failure due to extensive competition and lack of innovation in the products offered. The research focuses on Medan City MSMEs because these MSMEs are one of the largest provinces producing MSMEs in the Food and Beverage Industry, with a population of 1,828 MSMEs. The sample in the research was 95 MSMEs in Medan City which were taken using the Slovin formula. The data collection technique used in this research was carried out by distributing structured questionnaires using the SPSS v.28 application. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination R2. The research results show that there is a positive and significant influence of product innovation on business success, there is a positive and significant influence of competitive advantage on business success and there is a simultaneous positive and significant influence of product innovation and competitive advantage on the success of MSME businesses in Medan City.